FINANCIAL STATEMENT FRAUD DETECTION WITH FRAUD TRIANGLE ANALYSIS - Fitri Ella Fauziah (STIE Pelita Nusantara Semarang, 2022)
Fraud on financial statements can occur in any agency, including state-owned companies. The selection of BUMN as the research sample was due to the fraud cases occurring in BUMN. This study detects the occurrence of fraudulent financial statements with fraud triangle analysis. The purpose of this research is to analyze financial stability, external pressure, financial targets, monitoring effectiveness, nature of industry and auditor turnover for fraudulent financial statements. The analysis used was multiple regression, t-test and F-test. The research findings determined that external pressures and financial targets had an effect on financial statement fraud, but financial stability, monitoring effectiveness, the nature of the industry and auditor turnover gave the opposite result.